HUBUNGAN SELF EFFICACY TERHADAP KUALITAS HIDUP LANSIA DENGAN HIPERTENSI DI PUSKESMAS SEKIP PALEMBANG - Oscar Ari Wiryansyah; Meili Diana; Nuzula Firdaus (Jurnal Kesehatan dan Pembangunan, 2026)
Hypertension is a non-communicable disease that can negatively impact the health and quality of life of the elderly. Elderly individuals with uncontrolled hypertension are at risk of developing serious complications such as stroke and heart disease. Self-efficacy is a psychological factor that plays a crucial role in helping the elderly manage hypertension more effectively, including adherence to medication, maintaining a healthy diet, and implementing a healthy lifestyle. This study aims to analyze the relationship between self-efficacy and the quality of life among elderly people with hypertension at Sekip Public Health Center in Palembang. The research design is cross-sectional with a quantitative approach, involving 96 respondents selected through purposive sampling. The results showed that 74% of the elderly had high self-efficacy and 80.2% had a good quality of life. Statistical analysis using the Chi-Square test showed a significant relationship between self-efficacy and quality of life (p = 0.007; OR = 4.593). Elderly individuals with high self-efficacy are more likely to have a better quality of life compared to those with low self-efficacy. These findings suggest that efforts to enhance self-efficacy through education and social support can be an effective strategy to improve the quality of life of elderly individuals with hypertension. Training in stress management and support group facilitation is also necessary to further enhance their well-being.